2005
DOI: 10.1093/wber/lhi017
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Trade, and Foreign Direct Investment in Mexico

Abstract: Part of the rationale for the North American Free Trade Agreement was that it would increase trade and foreign direct investment (FDI) flows, creating jobs and reducing migration to the United States. Since poor data on illegal migration to the United States make direct measurement difficult, data on migration within Mexico, where census data permit careful analysis, are used instead to evaluate the mechanism behind predictions on migration to the United States. Specifications are provided for migration within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 44 publications
(45 reference statements)
3
41
0
3
Order By: Relevance
“…In general, there is a positive and statistically significant impact of migration on FDI; however, there are some differences regarding the education and skill level of migrants. Some authors found a positive and significant impact of highly educated migrants on FDI (Foley and Kerr 2008;Kugler and Rapoport 2007;Gheasi et al 2011), while others found a negative and significant impact (Aroca and Maloney 2005;Foad 2011). However, Foad (2011) relates his negative and statistically significant finding for college migrants to the nationality of those migrants.…”
Section: Empirical Findings On Foreign Direct Investmentmentioning
confidence: 99%
“…In general, there is a positive and statistically significant impact of migration on FDI; however, there are some differences regarding the education and skill level of migrants. Some authors found a positive and significant impact of highly educated migrants on FDI (Foley and Kerr 2008;Kugler and Rapoport 2007;Gheasi et al 2011), while others found a negative and significant impact (Aroca and Maloney 2005;Foad 2011). However, Foad (2011) relates his negative and statistically significant finding for college migrants to the nationality of those migrants.…”
Section: Empirical Findings On Foreign Direct Investmentmentioning
confidence: 99%
“…In contrast, the relationship between migration and FDI is an under-investigated area. A limited number of studies for example, Aroca and Maloney (2005), Tong (2005), Buch et al (2006), Kugler and Rapoport (2007), Bhattacharya and Groznik (2008), Javorcik et al (2010) and Federici and Giannetti (2010) have addressed this link, and they reported a positive and significant link between migration and FDI. Javorcik et al (2010) have shown that the stock of US FDI abroad is positively correlated with the presence of migrants.…”
Section: Introductionmentioning
confidence: 99%
“…Their study further indicates that the presence of migrants with a college education and of those with a higher education has a significant impact on FDI. It is interesting that a World Bank study shows that the outflows of FDI from the United States from a specific sector to a specific country are triggered by the existing share of laborers in that sector from that country (Aroca and Maloney, 2005). Next, Federici and Giannetti (2008) have also studied the link between migration and FDI, and they found a strong evidence of network externalities, which is mainly associated with the skilled diaspora.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil kajian mendapati bahawa faktor pelaburan asing telah berjaya menarik lebih ramai penduduk berhijrah ke kawasan destinasi tetapi wujud kekangan dari segi pembinaan di kawasan destinasi kerana ianya melibatkan perbelanjaan yang agak besar. Di Mexico, migrasi dan pelaburan asing berhubungan negatif antara satu sama lain kerana kemasukan pelaburan asing dilihat menjadi penghalang kepada penghijrahan penduduk dari kawasan lain (Aroca & Maloney 2005).…”
Section: Teori Zelinkyunclassified